Effects of Oil Price Shocks on the Economic Sectors in Malaysia - Shaari, Mohd Shahidan; Pei, Tan Lee; Rahim, Hafizah Abdul (International Journal of Energy Economics and Policy, 2013)
This paper aims to examine the effects of oil price shocks on economic sectors in Malaysia. A unit root test was conducted, in which data were shown to be non-stationary in all levels, and stationary in the first difference for all variables. The co-integration model was applied, and the results indicated that one co-integrating equation exists, suggesting the long-term effects of oil prices on the agriculture, construction, manufacturing, and transportation sectors. Finally, Grange causality test was performed, and the results implied that in Malaysia, oil price shocks can affect agriculture, similar to Hanson et al. (2010). Oil price instability also influences the performance of the agriculture sector, contrary to the results of Alper and Torul (2009). In addition, the construction sector was found to be dependent on oil prices. Therefore, the current study has an important implication for the Malaysian government in formulating policies on oil prices. The Malaysian government needs to control the price to ensure that unstable price will not harm the agriculture, manufacturing, and construction sectors. Keywords: oil price; agricultural, manufacturing and construction sectors. JEL Classifications: E31; E52; E62